2011
DOI: 10.1136/hrt.2010.216101
|View full text |Cite
|
Sign up to set email alerts
|

Apical right ventricular dysfunction in patients with pulmonary hypertension demonstrated with magnetic resonance

Abstract: Apical dysfunction appears to occur before global RVEF decreases in chronic PH, potentially constituting an early and sensitive marker of RV dysfunction in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
2
19
0
1
Order By: Relevance
“…Vogel-Claussen et al 29 found a significant correlation between MR-derived measurement RV septomarginal trabeculation mass, VMI (VMI = RV mass/LV mass), and RHC-documented PH hemodynamics. Fernandez-Friera et al 30 showed a regional difference in RV function and volumes as a result of chronic PH. They found that apical RV dysfunction appeared to occur even in the presence of normal global RV ejection fraction (RVEF) in patients with PH, in association with an increase in apical RV ESV.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Vogel-Claussen et al 29 found a significant correlation between MR-derived measurement RV septomarginal trabeculation mass, VMI (VMI = RV mass/LV mass), and RHC-documented PH hemodynamics. Fernandez-Friera et al 30 showed a regional difference in RV function and volumes as a result of chronic PH. They found that apical RV dysfunction appeared to occur even in the presence of normal global RV ejection fraction (RVEF) in patients with PH, in association with an increase in apical RV ESV.…”
Section: Resultsmentioning
confidence: 98%
“…(2) Some of the studies presented in this review [27][28][29][30][31][32] significantly correlating MR-derived parameters with RHC-measured hemodynamics and FC need to be validated in larger studies hypertension. Concomitant tricuspid regurgitation might explain the differences between RV systolic volume and pulmonary forward flow.…”
Section: Resultsmentioning
confidence: 99%
“…The author and colleagues found that basal RV ejection fraction (RVEF) did not differ between patients with mild or moderate PH. However, they showed that patients with moderate PH had significantly lower apical RVEF, with an apical RVEF<50% that was more sensitive than global RV dysfunction for the detection of PH [41]. In a study by López-Candalez et al using TDI and TDI derived strain in patients with severe PH, they found apical longitudinal strain most predictable for adverse outcome in those patients [42].…”
Section: Discussionmentioning
confidence: 97%
“…Both our group and Dambrauskaite et al [21][22][23] have previously shown that apical strain is related to disease severity in iPAH. Furthermore, Fernandez-Friera et al 24 demonstrated reduced apical RV ejection fraction-by magnetic resonance imaging-in adult iPAH patients. As apical remodeling and decreased longitudinal deformation were also found in PS-with normal global systolic RV function-it might be a sensitive echocardiographic marker of RV dysfunction.…”
Section: Rv Regional Remodeling and Functionmentioning
confidence: 99%